ZORA 159: Jezik ob meji in na meji - Bajzek Lukač, Marija (University of Maribor Press, 2025)
ZORA 159: Language Along and Across the Border. The scientific monograph Jezik ob meji in na meji (Language Along and Across the Border) focuses on sociolinguistic perspectives of the Prekmurje literary language, the Porabje dialect, lexicography, and the linguistic situation in the Rába Valley (Porabje). The monograph is divided into three chapters: (1) Language Along the Border, (2) Language in Dictionaries, and (3) Language Across the Border. The first chapter presents the development of the Prekmurje literary lan‑ guage from Evangelical literature to Catholic sacral writings and Ágoston Pavel’s grammar of the Prekmurje Slovene language. The second chapter comprises studies on lexicography, including the dictionary of the Gornji Senik (Felsőszölnök) dialect, the Comprehensive Hungarian–Slovene Dictionary, and Slovene geographical names in Porabje and the extended region. The third chapter presents sociolinguistic discussions on language strategies, the linguistic landscape and the status of the mother tongue (Prekmurje dialect, Porabje speech) in Porabje. Key findings of the monograph Jezik ob meji in na meji (Language Along and Across the Border) is that before the beginning of the 20th century, the Slovene language along the Rába River developed parallel with the Prekmurje variety. Porabje Slovene remains the language of everyday communication in Porabje families and among the older generations. However, to be preserved in Rába Valley region it deserves a special scinetific attention and further research.